Introduction: Failed Futures? (Post)-colonial Planning and Future-making in Tanzania - Lindner, Ulrike (Zamani: A Journal of African Historical Studies, 2024)
Future-making and planning as social practices are strongly related to the surrounding society’s political structures and power relations. In this special issue of ZAMANI, we conceptualize future-making as physical changes and social practices that shape future conditions by making future an issue in the present. We analyse how different approaches to the future, and also surprises and unintended side-effects, have informed the politics and practices of planning in Tanzania and its various regions. When we ask: “Failed Futures?” we address future in the plural, a term that has diffused into historical scholarship rather recently and originates from futurology/future studies, known as the interdisciplinary study of possible, desirable, and probable future developments and design options as well as their prerequisites. The term “futures” tries to capture the image of past spaces and different possibilities that historical actors can and could choose. As historians, we generally address past futures in such a sense that we look at past planning and future-making in order to understand the aspirations and hopes that were present at the time period we choose to analyse. Furthermore, if we look at the larger contexts among the future-making designs of past times, then interest groups and conjunctures of certain future horizons become visible and can be historically investigated.